PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN SIKAP SISWA DALAM HUBUNGAN INTERPERSONAL TEMAN SEBAYA KELAS VII SMP TRI BHAKTI PEKANBARU T.P 2014/2015 - Nurul Hazrina Nurul Hazrina; Elni Yakub Elni Yakub; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims 1) To determine of students’ increase attitude in relationships interpersonal peers level before the implementation of group counseling services. 2) To find out the on going process of the group counseling’s to the implementationin student attitude increase relationships interpersonal peers level of students. 3) To find out the students’ attitude in relationships interpersonal peers level after the implementation of group counseling service. 4) To find out the difference between pre and post group counseling services related to students’ attitude in relationships interpersonal peers level. 5) To determine whether there is influence of group counseling services students attitude incarease in relationships interpersonal peers.. The research was pre experimental research using one group pre- test and post- test design. The subjects of the research were the grade VII students of Tri Bhakti Junior High School Pekanbaru with the total population of 144 students. The writers took 30 students as samples by using purposive sampling. In collecting data, the writers used questionnaires. Based on calculations obtained correlationcoefficient r = 0.52 and the coefficient of determination r2 = 0, 27. It can be seen that tcalculation is greater than with significance level of 5% (11.79 > 2.000) so Ho rejected and Ha accepted , which means a significant difference to the improvement of student attitudes in interpersonal relationships peers before and after conducted group counseling services.Key Words : Group Counseling Services, Attitude, Interpersonal Relationships